Prove the property: log_a(x) + log_a(y) = log_a(xy).

The derivation of the property starts with the basic representation of logarithms as powers. Lets consider a^(log_a(xy)). Then, a^(log_a(xy)) = xy. However, x = a^(log_a(x)) and y = a^(log_a(y)). Therefore, xy = a^(log_a(y)) * a^(log_a(x)) = a^(log_a(x) + log_a(y)). Hence, log_a(x) + log_a(y) = log_a(xy).

Related Maths A Level answers

All answers ▸

Find an expression in terms of powers of cos(x) for cos(5x)


Integrate x((x^2)+2) dx


A curve C with an equation y = sin(x)/e^(2x) , 0<x<pi has a stationary point at P. Find the coordinates ofP?


find x: e^(3x-9) = 8


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences